Design of a local bump feedback system for a variably polarizing undulator - Bizen, T (Journal of synchrotron radiation, 1998)
A local bump feedback system is under construction to correct the orbit distortion caused by the magnetic field errors of a double-array undulator used to generate linear and circular polarization of light for a soft X-ray beamline. The local bump orbit is created by steering coils several turns long and four sets of steering magnets. The kick angle of the long steering coils and the steering magnets is determined according to the motion of the undulator and by detecting the beam position